Sarius cups from Žuta Lokva (Roman Dalmatia – Croatia). Preliminary report - Ožanić Roguljić, Ivana; Mantovani, Valentina (Rei Cretariae Romanae Fautorum Acta, 2022)
Žuta lokva is a site on the road Senia - Siscia (the road is mentioned in Itinerarium Antonini, Tabula Peutingeriana) in the hinterland of Roman Dalmatia (Lika county, Croatia). During rescue excavations that ended in 2002 a building (dim. 10 x 25 m) was revealed. The remains are badly preserved and they probably belonged to a caupona, diversorium or hospitium on a road. The site is dated from the beginning of the 1st century to the first half of the 2nd century AD. Analysis of the pottery showed that most of the vessels belonged to tableware – specially drinking vessels like Sarius cups, thin walled pottery of different origin and lead glazed vessels.